La Mortalite Infanto-Juvenile A Bouafle : Contribution A L’analyse Des Conditions De Vie Dans Une Ville Ivoirienne - Kadet G. Bertin; Adjelou Kessou; Anoh Kouassi Paul (European Scientific Journal, ESJ, 2018)
The dynamics of Bouaflé, an urban locality in the center-west of Côte d'Ivoire, faces a double challenge. On the one hand, the plight related to the mortality of the under-five stands out as a threat to their future. On the other hand, owing to lack of drinking water in the city as well as harmful effects of polluting activities on the local environment, environmental pathologies affect the urban space. From available documents on this city supplemented by field surveys, this study showcases an inventory of the determining factors of infant and child mortality in Bouaflé and highlights the limitations of local governance in the quest for a sustainable development for the capital city of the Marahoué.